The Role of Teachers in Improving the Learning Focus of Children with Special Needs at Mitra Inalum Kindergarten - Anggreni Anggreni; Niswa Hasanah (Universitas Islam Negeri Sumatera Utara, 2025)
The focus of learning for children with special needs is the concentration of attention on lessons, learning materials, and the process of acquiring them carried out by children who require special behavior in following the learning process. This study aims to help children with special needs to stay focused in the learning process. The method used in this study is qualitative research with data collection techniques namely interviews, observation, and documentation. The results of the study show that first, the implementation of learning at TK Mitra Inalum Tanjung Gading, Sei Suka District, Batubara Regency is with PAIKEM learning (Active, Innovative, Creative, Effective and Fun Learning); second, the focus of learning for children with special needs during learning there is a significant difference between the focus of learning for normal children and the focus of learning for children with special needs. When the teacher delivers the teaching material, normal children always focus on the teacher's delivery. While children with special needs are sometimes able to focus and sometimes not. So the homeroom teacher is assisted by a companion teacher so that children can focus on following the learning process.; and third, the efforts of teachers in addressing the learning focus of children with special needs at the Inalum Tanjung Gading Partner Kindergarten, Sei Suka District, Batubara Regency, namely by preparing educational game tools, brain gymnastics, audio-visual learning media, assistance from accompanying teachers, and mini parenting.